Cervical Screening: women's resistance to the official discourse - Armstrong, Natalie (2005)
This study is an empirical exploration of Foucault's theoretical ideas on resistance, through a case study of cervical cancer screening and women's responses to the official discourse surrounding it. In England, this form of screening is organised through a national programme and consistently achieves coverage of over 80%. Given this high attendance it may appear that any resistance is negligible. However, this thesis argues that such a focus on attendance, or behaviour, is misguided and that, by focusing attention on the level at which the official discourse on screening is interpreted, understood and made sense of by individual women, it is possible to identify instances of thought and talk based resistance.